2001
DOI: 10.1017/s1367943001001354
|View full text |Cite
|
Sign up to set email alerts
|

Attracting endangered species to ‘safe’ habitats: responses of fairy terns to decoys

Abstract: The New Zealand fairy tern (Sterna nereis davisae) is considered an endangered subspecies. The aims of this study were to quantify fairy tern responses to decoys and sound recordings and determine the viability of decoys as a technique for re-establishment of this species in protected habitat. Sixteen decoy trials were conducted in an area suitable for nesting from 9 September to 2 October 1999 at Papakanui Spit, New Zealand (36°26′S, 174°13′E). The decoy models were effective in attracting fairy terns to a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…As a result, birds were attracted and founded new colonies. This technique has been used successfully on a number of colonial bird species (Podolsky 1990; Podolsky & Kress 1992; Blokpoel et al 1997; Jeffries & Brunton 2001; Martinez‐Abrain et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, birds were attracted and founded new colonies. This technique has been used successfully on a number of colonial bird species (Podolsky 1990; Podolsky & Kress 1992; Blokpoel et al 1997; Jeffries & Brunton 2001; Martinez‐Abrain et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is expected to operate broadly in breeding habitat patch choice of social animals such as colonial birds (Shields et al 1988, Forbes and Kaiser 1994, Sarrazin et al 1996. In fact, the use of decoys and taped vocalizations have been used successfully in seabirds to attract individuals and create new colonies in previously vacant areas (e.g., Kotliar and Burguer 1984, Kress and Nettleship 1988, Podolsky 1990, Jeffries and Brunton 2001. Recently, it was suggested that individuals could use the local reproductive success of conspecifics in the past as an index of patch quality (''performance-based attraction hypothesis,' ' Danchin and Wagner 1997).…”
Section: Introductionmentioning
confidence: 99%
“…We found evidence of UV reflectance of skin but not plumage that was not detectable by humans, and this may need to be taken into account when attempting to replicate seabird colorations, e.g. when building model decoys for attracting seabirds to newly restored nesting sites (Jeffries & Brunton ). Although studies on UV perception are rare in seabirds, a few studies have identified UV‐sensitive vision in the Chardriiformes (e.g.…”
Section: Discussionmentioning
confidence: 90%